Insights into the Fabrication and Electrochemical Aspects of Paper Microfluidics-Based Biosensor Module - Kumari R.; Singh A.; Azad U.P.; Chandra P. (My University, 2025)
Over the past ten years, microfluidic paper-based analytical devices (micro-PADs) have attracted a lot of attention as a viable analytical platform. It is expanding as a result of advances in manufacturing processes and device integration. Conventional microfluidics approaches have some drawbacks, including high costs, lengthy evaluation times, complicated fabrication, and the necessity of experienced employees. Hence, it is extremely important to construct a detection system that is quick, affordable, portable, and efficient. Nowadays, micro-PADs are frequently employed, particularly in electrochemical analyses, to replicate the classic standard laboratory experiments on a miniature paper chip. It has benefits like rapid assessment, small sample consumption, quick reaction, accuracy, and multiplex function. The goal of this review is to examine modern paper microfluidics-based electrochemical sensing devices for the detection of macromolecules, small molecules, and cells in a variety of real samples. The design and fabrication of micro-PADs using conventional and the latest techniques have also been discussed in detail. Lastly, the limitations and potential of these analytical platforms are examined in order to shed light on future research. © 2023 by the authors.